PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA KANTOR CAMAT BATAM KOTA - Ndruru, Titus Tulus Hati; Dompak, Timbul (SCIENTIA JOURNAL, 2023)
This study aims to determine the effect of Motivation and Work Discipline on the Performance of employees in the Batam City District Office. The research method used is explanatory and quantitative in nature. The sampling technique used was saturated sampling technique, namely the sample in this study consisted of 40 employees who served in the Batam City District Office. The instrument used in the study was a questionnaire by distributing questionnaires to respondents. Data were processed using SPSS software version 29 with the results showing that motivation has a positive but not significant effect on employee performance with t count 0.199 < t table 2,0261 ​​and a significance of 0.843 > 0.05. Work Discipline obtained t count value of 7,823 > t table 2,0261 ​​with a significance of 0.00 < 0.05 which means that Work Discipline has a positive and significant effect on employee performance. Motivation and Work Discipline simultaneously have a positive and significant effect on Employee Performance, this is evidenced by the value of the F test results with F count 40.164 > F table 3.25 and a significance of 0.000 < 0.05. And the R-Square value is 0.685.